Invigorasi Benih Tomat (Lycopersicum esculentum Mill) Kadaluarsa Dengan Aplikasi Air Kelapa Muda Dan Lama Inkubasi - Junaidi Junaidi; Iskandar Lapanjang; Bahrudin Bahrudin (Mitra Sains, 2018)
This research aims to know the influence of granting young coconut water and long incubation as well as combination against tomato seeds vigor expired. This research was carried out in the village of Tinggede sub-district of Marawola Regency Sigi Central Sulawesi province, October to December 2016. Factor i: grant of young coconut water which consists of 3 levels; K0: without young coconut water (control), K1: young coconut water concentration of 15%, K2: young coconut water concentration of 30%. Factor II: Long incubation which consists of 3 levels; W1: Long incubation 1 h, W2: Long 2-hour incubation, W3: Long incubation of 3 hours. This research consists of 9 combination treatment and each treatment was repeated as many as 3 times so it takes 27 block research. The results showed that a single factor of influence real young coconut water against a potential of growing power, germinate, grow, grow keserempakan speed, high number of seeds and leaves of tomato seedlings for expiration. The best coconut water treatment i.e. the concentration of 30%. Long incubation effect real against potential grows, the power, the speed of growth and germinate keserempakan grow tomatoes for expired, the old treatment the best incubation that is 2 hours. While the interaction treatment concentration of young coconut juice with a long incubation gives no real influence against tomato seeds vigor expired.